Associations between brain morphology and motor performance in chronic neck pain: A whole‐brain surface‐based morphometry approach. Issue 14 (20th June 2019) - De Pauw, Robby; Coppieters, Iris; Caeyenberghs, Karen; Kregel, Jeroen; Aerts, Hannelore; Lenoir, Dorine; Cagnie, Barbara
Abstract: Changes in brain morphology are hypothesized to be an underlying process that drive the widespread pain and motor impairment in patients with chronic neck pain. However, no earlier research assessed whole‐brain cortical morphology in these patients. This case–control study assesses group‐differences in whole‐brain morphology between female healthy controls (HC; n = 34), and female patients with chronic idiopathic neck pain (CINP; n = 37) and whiplash‐associated disorders (CWAD; n = 39). Additionally, the associations between whole‐brain morphology and motor performance including balance, strength, and neuromuscular control were assessed. Cortical volume, thickness, and surface area were derived from high resolution T1‐weighted images. T2*‐weighted images were obtained to exclude traumatic brain injury. Vertex‐wise general‐linear‐model‐analysis revealed cortical thickening in the left precuneus and increased volume in the left superior parietal gyrus of patients with CINP compared to HC, and cortical thickening of the left superior parietal gyrus compared to HC and CWAD. Patients with CWAD showed a smaller cortical volume in the right precentral and superior temporal gyrus compared to HC. ANCOVA‐analysis revealed worse neuromuscular control in CWAD compared to HC and CINP, and in CINP compared to HC. Patients with CWAD showed decreased levels of strength and sway area compared to CINP and HC. Partial correlation analysis revealed significant associations between the volume of the precentral gyrus, and neuromuscular control and strength together with an association between the volume of the superior temporal gyrus and strength. Our results emphasize the role of altered gray matter alterations in women with chronic neck pain, and its association with pain and motor impairment.